6’-sialyllactose ameliorates the ototoxic effects of the aminoglycoside antibiotic neomycin in susceptible mice - Abou Assale, Tawfik; Kuenzel, Thomas; Schink, Tamara; Shahraz, Anahita; Neumann, Harald; Klaus, Christine (Frontiers in Immunology, 2023)
Sialic acids are terminal sugars of the cellular glycocalyx and are highly abundant in the nervous tissue. Sialylation is sensed by the innate immune system and acts as an inhibitory immune checkpoint. Aminoglycoside antibiotics such as neomycin have been shown to activate tissue macrophages and induce ototoxicity. In this study, we investigated the systemic subcutaneous application of the human milk oligosaccharide 6’-sialyllactose (6SL) as a potential therapy for neomycin-induced ototoxicity in postnatal mice. Repeated systemic treatment of mice with 6SL ameliorated neomycin-induced hearing loss and attenuated neomycin-triggered macrophage activation in the cochlear spiral ganglion. In addition, 6SL reversed the neomycin-mediated increase in gene transcription of the pro-inflammatory cytokine interleukin-1β (Il-1b) and the apoptotic/inflammatory kinase Pik3cd in the inner ear. Interestingly, neomycin application also increased the transcription of desialylating enzyme neuraminidase 3 (Neu3) in the inner ear. In vitro, we confirmed that treatment with 6SL had anti-inflammatory, anti-phagocytic, and neuroprotective effects on cultured lipopolysaccharide-challenged human THP1-macrophages. Thus, our data demonstrated that treatment with 6SL has anti-inflammatory and protective effects against neomycin-mediated macrophage activation and ototoxicity.